Bridging the gap between fisheries science and society: exploring fisheries science as a social activity. (23rd December 2016) - Bailey, Jennifer L.; Liu, Yajie; Davidsen, Jan Grimsrud
Abstract : Much has been written about the poor relations between fisheries scientists and lay people, but the experience of two field biologists suggests that good relations can exist and have a positive impact on the exchange of knowledge across the "science"—"society" divide. This article is a first attempt to map the contact points between fisheries scientists and lay people and to explore the spin-offs these can have. It presents the results of two surveys conducted with participants at the November 2015 MYFISH/ICES Symposium on "Targets and limits for long term fisheries management": a real-time Kahoot survey of the audience and a longer, on-line survey some participants filled out following the symposium session. The survey results generally support the supposition that fisheries scientist-society interactions are extremely varied and that much in the way of information exchange and mutual learning can occur. However they also show that trust issues remain in the fisheries management community, but not just between scientists and lay people: fisheries managers and environmental non-governmental organizations may be less trusted by scientists than are lay people. The study concludes by discussing how future studies should be designed and focused and with an invitation for comments from the ICES community.